Low Fat High Protein Sosis Berbahan Dasar lawi-lawi (Caulerpa racemosa) sebagai Inovasi Kuliner Sehat Khas Makassar dan Makanan Alternatif bagi Anak Penderita Obesitas - Mukarramah Mukarramah; Wahyuni Wahyuni; Emilia Emilia (Hasanuddin University, 2017)
South Sulawesi has great potential of marine resources. This makes the commodity of the sea as one of the mainstay sources of local revenue in South Sulawesi. Riskesdas 2013 results show that the incidence of obesity among the main children at the age of 5-12 years reached a percentage of 18.8%. Seaweed C. racemosa is a food rich in protein and amino acids, rich in soluble or insoluble fiber, and low in fat, so it has the potential to be processed into an alternative food for obese people. One type of processed foods that children favor today is the sausage. Sausages are generally made from beef or chicken meat. Accordingly, it is developed innovation of sausage products made from seaweed Caulerparacemosa as an alternative food of obese people as well as a healthy culinary typical of Makassar, South Sulawesi, which is rich in fiber but low in fat. This research is conducted by the stages of sausage formulation and then the product is tested by organoleptis and hedonic. From this research, it can be concluded that the best Low Fat High Protein sausage formulation is the 2nd formula (F2) with the main composition of tapioca substitution of lawi-lawi (Caulerparacemosa) porridge, as compared to F1 with lawi-lawi powder composition (Caulerparacemosa). The panelist's favorite presentation in general is F1: 65%; F2: 75%, and protein content of F1: 3,87%; F2: 3.93%, and fat content of F1: 5.02%; F2: 7.89%.Keywords: Lawi-lawi, Caulerparacemosa, sausage, obesity